1985
DOI: 10.3109/01485018508987281
|View full text |Cite
|
Sign up to set email alerts
|

Do Nonspermatozoal Cells Mainly Stem from Spermiogenesis? Study of 106 Fertile and 102 Subfertile Men

Abstract: The various nonspermatozoal cell types in the semen of 106 fertile (F) and 102 subfertile (SF) men were described and their relative proportions estimated. About 94% (F) and 90% (SF) were found to be germinal elements, among which, respectively, about 27% and 51% were spermatids, 48% and 36% residual bodies, 19.4% and 2.6% primary spermatocytes, 0.03% and 0.61% spermatogonia. The epithelial cells and blood cells represented about 6% (F) and 10% (SF) of the nonspermatozoal cells; in F men 5.3% and in SF men 9.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
2
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
3
14
2
1
Order By: Relevance
“…It has been shown that germ cells constitute the main component of non-sperm cells in semen from men without infections (Auroux et al 1985, Jassim & Festenstein 1987, Smith et al 1989. Moreover, it has also been reported that purified immature germ cells isolated from semen samples could be useful for diagnostic and research purposes (Gandini et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that germ cells constitute the main component of non-sperm cells in semen from men without infections (Auroux et al 1985, Jassim & Festenstein 1987, Smith et al 1989. Moreover, it has also been reported that purified immature germ cells isolated from semen samples could be useful for diagnostic and research purposes (Gandini et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…They often contain 2 or more haploid nuclei (Table 1) and therefore may be confused with polymorphonuclear granulocytes (PMN). Auroux et al [5] found a higher concentration of spermatids in semen samples from subfertile than from fertile men. Another study showed an inverse association between the primary spermatocyte/spermatid ratio and the sperm concentration [36].…”
mentioning
confidence: 99%
“…Anucleate bodies are the most frequently occurring nonsperm cell elements in the semen [5]. Occasionally, these anucleate bodies contain membraneous organelles [77], in which case they are called residual bodies.…”
mentioning
confidence: 99%
“…Leucocytospermia, defined as 61 million peroxidase-positive leucocytes/ml of semen [4], has been associated with poor semen quality and genital tract infections [5]. Leucocytospermia is more common in subfertile than in fertile men [6] and is associated with impaired sperm motility [7]. The accessory sex gland functions are also impaired in subjects with leucocytospermia [8].…”
Section: Introductionmentioning
confidence: 99%